Using nested PCR to improve detection of earthworm eDNA in Canada. (October 2017) - Jackson, Mason; Myrholm, Colin; Shaw, Cindy; Ramsfield, Tod
Abstract: Earthworms that are invasive to Canada's boreal forest are mainly from the family Lumbricidae and they have the potential to change ecosystem carbon sequestration and biodiversity. Traditional methods used to survey earthworms rely on finding specimens, consume large amounts of time and labour, and are expensive. A sensitive genetic method to detect earthworm DNA in soil would provide a fast, relatively low cost method for earthworm survey. In this study, PCR primers were used to detect earthworm DNA from earthworm tissues and soil samples. Though single PCR yielded only faint signals from soil samples, a nested PCR method allowed strong detection in native and cultivated forest soils, including those archived for more than 30 years, providing a promising technique for genetic monitoring of earthworms in the boreal region of Canada. Highlights: Nested PCR was used to improve detection of earthworm DNA in soil. Earthworm DNA was detected in archival soil samples stored up to 30 years. Nested PCR for detection of earthworm DNA is cost effective for ecological studies.